THE PHENOMENON OF SLANG LANGUAGE ON FACEBOOK AND TWITTER - Zaka, Istifatun (ELTICS Journal, 2015)
This paper describes about the phenomenon of slang language on social network, namely facebook and twitter. Slang in this paper belongs to sociolinguistics study, especially sociolect. This is a descriptive qualitative method, which consists of three phase: data collection, data analysis, and presentation of the result of data analysis. The data were collected by observing the netters utterance. Data were analysed through two phases. First, analyzing the meaning of the slang. Second, was analysing the categories of the slang. There are four point findings in this study. Firstly, the various forms of slang expression units are words and phrases. Secondly, the variety of linguistic processes forming units slang expression are by adding sound, erasing sound, changing vocal, replacing consonant, shifting sound, returning sound, repeating, and changing spell. Thirdly, the source languages of various slang reference units are from national language, regional languages, and foreign languages. Fourthly, the communicative functions of various units of slang expressions are informative function, directive function, expressive function, komisif function, phatic function, and poetic function. Finally, from the finding of those four points in this study, we know that slang language on facebook and twitter has its own uniqueness compared to other types of language. Â  Keyword: slang, facebook and twitter, forms of slang, linguistic processes, source languages, communicative functions.